Science Research Olympiad Preparation Assistance: Application of Differential and Integral in Radioactive Decay - Prabowo, Agung; Chandra, Novita Eka; Juliza, Melda; Arumningtyas, Felinda (International Journal of Research in Community Services, 2025)
Performance not only a source of pride for students, but also for schools. The Indonesian Student Research Olympiad (OPSI) is a national-level activity recognized by the National Achievement Center (PUSPRESNAS). Schools need to provide guidance to support their students in participating in OPSI competitions, one of which is in mathematics. The purpose of this community service is to provide new learning experiences to students at SMA Negeri 1 Mirit, Kebumen Regency, in managing real-world problems and using mathematics to find solutions. Examples given are the problem of medication timing and radioactive decay. The community service method consists of material presentation, class discussions, and providing examples of problems that can be solved using similar methods. The community service is carried out once for 2 hours, the results of the community service are measured by a questionnaire, and of the 20 students who participated in the activity, all agreed that this community service provided a new learning experience that was different from the learning experience during the lessons.